The Effect of Responsive and Proactive Market Orientation on Product Innovation and Company Performance: A Case Study on MSMEs in the Culinary Field in D.I. Yogyakarta - A’bdul Fatach Ichwan; Siti Nursyamsiah (Integrated Journal of Business and Economics (IJBE), 2019)
This study aims to determine the effect of Responsive and Proactive Market Orientation on Product Innovation and Company Performance. The population in this study is the Micro, Small, and Medium Enterprise (MSME) in the Culinary Division at D.I. Yogyakarta and use 200 respondents as a sample. By using convenience sampling technique, the researchers have the freedom to choose any culinary MSME found around D.I. Yogyakarta to be the respondent. Hypothesis testing using Structural Equation Model (SEM) analysis. The findings show that there is a positive influence of responsive market orientation on product innovation performance, proactive market orientation on product innovation performance, product innovation performance on the company's market performance, and the company's market performance on the company's financial performance. The findings of this study contribute to MSMEs that information about market orientation adopted by business actors or companies can affect the performance of new product innovations in the market to improve the company's market performance which then affects the company's financial performance.